Analysis of the Implementation of the Teaching Campus Program on Students' Literacy and Numeracy Skills - Amalya, Rahma; Zufriady, Zufriady; Permana, Dede (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the improvement of students' literacy and numeracy skills through the Teaching Campus Program Batch 8 at SDIT Al-Manar Pekanbaru. This program is part of an effort to improve the quality of education by involving university students as teachers in target schools. The study uses a descriptive qualitative research method with a case study approach. The research subjects consist of 10 participants. In this study, the primary instrument is the researcher themselves, and supporting instruments include observation, interviews, documentation, as well as pre-tests and post-tests from AKM. Data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions. The results of the pre-test and post-test AKM show that students who achieved the